EVALUATING THE EFFECTIVENESS OF INTERACTIVE LEARNING TECHNOLOGIES IN ENHANCING SPATIAL THINKING AMONG MATHEMATICS STUDENTS - Borboeva, Gulnisa; Sooronbaeva, Kaukhar; Kalbekova, Makhpurat; Seiitkazyeva, Gulnara; Sarygulova, Nurkyz (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
The study's purpose was to assess the impact of combining traditional and interactive teaching methods on students' capacity to visualise, manipulate, and transform three-dimensional objects, while also improving their spatial representation and problem-solving skills in geometry. The research monitored 132 students studying mathematics of varying proficiency levels over a semester, employing spatial imagination tasks to improve visualisation abilities. Pre- and post-assessments measured enhancements in spatial reasoning. Methods integrated interactive tools (3D modelling, simulations) with conventional geometry tasks. The study revealed that students using interactive teaching methods, including 3D modelling and computer simulations, exhibited markedly superior enhancements in spatial reasoning relative to those adhering to conventional methods. The experimental group, utilising interactive tools, attained superior scores in spatial thinking assessments, with 60% of students exceeding 70 points, in contrast to merely 35% in the control group. Furthermore, students in the experimental group indicated reduced task complexity and increased satisfaction with the learning methodologies. The findings indicate that interactive methods significantly improve students' capacity to visualise and manipulate geometric entities, thereby enhancing their spatial reasoning abilities. This study demonstrates that a combination of traditional and interactive teaching methods enhances the spatial skills essential for successful mathematical training.